COMPETENCE OF THE HEAD OF AN EDUCATIONAL INSTITUTION AND ITS MANAGEMENT POSSIBILITIES IN COVID-19 CONDITIONS - Mikaskina, Inese; Arbidane, Iluta; Padalka, Oleh; Arbidans, Arvis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Competence of the head of an educational institution and its management During the Covid-19 pandemic, a large number of different legal acts and measures are required. They require a large amount of diligence and immediate action in the application of new regulations. All innovations require regular reporting on progress, thus adding to the workload of staff. The results of the research show that a modern school principal does not have enough only pedagogical competences, but at the same time must be both a leader who guides the team towards the goal, and a manager with a strategic vision, the ability to plan and implement these plans, in addition, one must be able to navigate legal acts and their application. The aim of the research: to study the competence of the head of an educational institution and its management possibilities in the conditions of COVID-19. Research tasks: to study the normative regulation of the education system; to perform the analysis of the competence of the head of the educational institution in the conditions of COVID-19; to study the impact of the measures and restrictions introduced by COVID-19 on the management context of the educational institution; summarization and analysis of the obtained survey data. Research methods: scientific literature, internet sources, documents and statistical data research, data processing and analysis of the results of the survey data.